ANALISIS STRUKTUR INDUSTRI SUSU DI INDONESIA - Susila, Ihwan (Universitas Muhammdaiyah Surakarta, 2003)
Decision for a strategy needs circumstantial analysis from environment of external and internal situation. There are two important situations which need considered. First, industrial condition and its emulation. Second, company capability to compete, resource, strength and internal feebleness, and the market position. All peripatetic organization in macro environment having major effect to company strategy. Such macro environment according to Thompson and Stricland (2003) for example: free economics, demography, social values and the life style, legislation and governmental regulation, and the technological factors. From other side macro environment, a business organization given on by environment of emulation and direct interconnected industry with company. According to Porter (1980), there are five very strength have an effect on to determination of company strategy in a industry in order to earn to own competing excellence that is: suppliers, new comer in industry, buyer, company of competitor and other; dissimilar company offering substitute product. The factors give pressures in emulation which influence compared by stronger of other macro factor industrial growth of milk in Indonesia nor quit of factors or strength and emulation pressures. During the time productivity of raw material of milk that is fresh milk in Indonesia still be pertained by lower, so that not yet earned to fulfill national requirement.